PENGARUH E-COMMERCE TERHADAP PERTUMBUHAN EKONOMI INDONESIA - Rr. Getha Fety Dianari (Center for Economic Studies Universitas Katolik Parahyangan, 2018)
The rapid development of information and communication technology has caused the emergence of a new economy, indicated by the phenomenon of internet-based businesses or e-commerce. This research uses the Auto-Regressive Distributed Lag (ARDL) approach to analyzes the impact of e-commerce on Indonesia’s economic growth in 1996-2015. The results show that the development of e-commerce as represented by the increase of the number of e-commerce transaction value, the increase of the number of business websites, and the number of internet users is proven to bring positive impact on Indonesia’s economic growth. This validates the hypothesis which states the increasing number of e-commerce transaction value, which is formed by the interaction between business websites as the supply indicator and the internet users as the demand indicator, shall bring enhancement to the intensity of macroeconomic activities. However, the effect is only significant for the long-run relationship but is not significant in the short-run relationship. Keywords: e-commerce; economic growth; ARDL